Exploring the relationship between calcitonin, ionized calcium, and bone turnover in cats with and without naturally occurring hypercalcemia - Maniaki, Evangelia; Pineda, Carmen; Hibbert, Angie; Finch, Natalie (Frontiers in Veterinary Science, 2024)
This case-control study aimed to evaluate calcitonin response in naturally occurring hypercalcemia in cats and assess the relationships between calcitonin and ionized calcium (iCa) and examine relationships between calcitonin, iCa and bone turnover. Hypercalcemic cats (persistently increased iCa concentration [>1.40mmol/l]) were identified retrospectively via a medical database search; additional hypercalcemic and normocalcemic cats were recruited prospectively. Data regarding routine biochemical and urine testing, diagnostic imaging and additional blood testing were obtained. Serum alkaline phosphatase (ALP) activity was used as a marker of bone turnover. Serum calcitonin concentration was analyzed using a previously validated immunoradiometric assay. Hypercalcemic cats with an increased calcitonin concentration (>0.9ng/L) were termed responders. Group comparisons were performed using a Mann-Whitney test for continuous variables and a χ2 test for categorical variables. Spearman's correlation coefficient was used to examine the relationships between calcitonin, iCa and ALP. Twenty-six hypercalcemic and 25 normocalcemic cats were recruited. Only 5/26 (19.2%) of the hypercalcemic cats were identified as responders, and all were diagnosed with idiopathic hypercalcemia. There was no significant correlation between the concentrations of calcitonin and iCa (P = 0.929), calcitonin and ALP (P = 0.917) or iCa and ALP (P = 0.678) in hypercalcemic cats, however, a significant negative correlation was observed between calcitonin and ALP (P = 0.037) when normocalcemic and hypercalcemic cats with an elevated calcitonin concentration were analyzed together. The expected increase in calcitonin concentration was present in only a small subset of hypercalcemic cats; no correlation was found between iCa and calcitonin concentration. The inverse relationship between calcitonin and ALP in cats with increased calcitonin concentrations suggests that the ability of calcitonin to correct hypercalcemia may be related to the degree of bone turnover.